Potensi dan Tantangan Reksa Dana Syariah di Indonesia dalam Menghadapi Perubahan Ekonomi Global - Mukhlisotul Jannah; Fany Cahyaningsih; Ramanda Setiawan; Abi Fauzy, Muhammad (RUBINSTEIN, 2025)
The Islamic Capital Market in Indonesia has shown significant development since its introduction in 2000, marked by the launch of the first Islamic mutual fund product. This study aims to analyze the development of the Islamic capital market, particularly in the context of Islamic mutual funds in Indonesia, as well as the challenges and opportunities faced during its growth. The method used in this research is a literature review, examining various academic sources and reports related to the Islamic capital market in Indonesia. The findings indicate that although Indonesia’s Islamic mutual fund market remains relatively small compared to countries like Malaysia, there has been a growing public interest in Sharia-compliant investments, especially among the younger generation. Additionally, related sectors such as Islamic banking and halal technology have contributed to the growth of this market. Nevertheless, the market still faces several challenges, including high volatility and risks associated with global economic instability, as evidenced during the Covid-19 pandemic. The conclusion of this study is that Indonesia's Islamic mutual fund market holds great potential for further development. However, it requires product innovation and policy advancement to improve its international competitiveness, while ensuring compliance with fair and sustainable Sharia principles.